2023
DOI: 10.1021/acsnano.2c11680
|View full text |Cite
|
Sign up to set email alerts
|

Active Synthetic Microrotors: Design Strategies and Applications

Abstract: Microrotors are microscopic objects that convert energy stored in the environment into spontaneous rotation, in the form of spinning along an axis, rolling on a surface, or orbiting in circles. Because of its distinct dynamics and the vertical flows around it, a microrotor is potentially useful for applications, including drug delivery, minimally invasive surgery, fluid mixing, and sensing. It is also useful as a model system to probe the collective behaviors among rotating microobjects. In this review article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 194 publications
0
5
0
Order By: Relevance
“…Some studies have demonstrated programmed rotary motion by appropriately designing catalytic swimmers. [96] Previous research has also shown the feasibility of single chemotactic events, enabling swimmers to move toward higher fuel concentrations of the surrounding environment. [52,94,97] To achieve full autonomy, the next step is enabling directional changes in movement by adjusting the propulsion mechanism in response to the surrounding environment, similar to natural microorganisms, which exhibit dual chemotaxis (positive and negative chemotaxis) in response to chemical cues.…”
Section: Fundamentals Of Multilocomotion Mechanismmentioning
confidence: 99%
“…Some studies have demonstrated programmed rotary motion by appropriately designing catalytic swimmers. [96] Previous research has also shown the feasibility of single chemotactic events, enabling swimmers to move toward higher fuel concentrations of the surrounding environment. [52,94,97] To achieve full autonomy, the next step is enabling directional changes in movement by adjusting the propulsion mechanism in response to the surrounding environment, similar to natural microorganisms, which exhibit dual chemotaxis (positive and negative chemotaxis) in response to chemical cues.…”
Section: Fundamentals Of Multilocomotion Mechanismmentioning
confidence: 99%
“…Note that we are focusing on the torques exerted by a moving nano/micromotor on its neighbors, rather than on itself, which makes it a rotor that is beyond the scope of this work. [13][14][15] We report in this communication that a chemically powered nano/micromotor spins nearby tracers, so that a tracer moves along with the nanomotor and spins in place (in the co-moving frame), unlike the tracers in ref. 16 and 17 that orbit in large convective loops.…”
mentioning
confidence: 93%
“…Note that we are focusing on the torques exerted by a moving nano/micromotor on its neighbors, rather than on itself, which makes it a rotor that is beyond the scope of this work. 13–15…”
mentioning
confidence: 99%
“…53 MD simulations have confirmed that droplets on a superhydrophobic surface will roll when a body force is applied. 54 Although the concept of microrotor rotation and rolling under a rotating electric field has been reported, 55 the rolling mechanism of nanodroplets under a rotating electric field has still not been investigated in detail, and the effect of the solid surface on the rolling transport of the droplets is still unclear. Here, we studied the rolling transport of nanodroplets on a hydrophobic surface under a rotating electric field by MD simulations.…”
Section: ■ Introductionmentioning
confidence: 99%